The decline of mbira performances in families: a case study of Mhuri yekwa Gumira of Zihute kraal in Murehwa - Dondo, Matlidah Garikayi (Midlands State University, 2018)
This research is a case study which was conducted in Zihute Kraal in Murehwa district. The study focuses on the decline of mbira performances in families concentrating mainly on Mhuri yekwa Gumira Mbira Performers who were great mbira players around the 1960s and released a single entitled Wanyanya. The study investigated the factors that contributed to the decline of mbira playing amongst the group members. In order to gather essential data on what caused once vibrant mbira groups to abandon the mbira playing tradition, an ethnographic research was engaged. Snow ball and purposive sampling techniques were used to select the participants for the study in the Zihute Kraal in Murehwa. Face to face semi structure interviews, observation, video recordings, field notes are the instruments which were used to capture data. In the study the researcher noted that Christianity and other factors brought by colonialism contributed greatly to the decline of mbira performances by Mhuri yekwa Gumira. Many family members and people in the community converted to Christianity as a result many people disassociated themselves from a religion that was regarded as pagan. Apart from Christianity other reasons are also highlighted such as searching for employment, resettlement programs, financial constraints and failure to receive royalties from recorded works. The study recommends that old mbira songs need to be revived by means of digitalizing them to make the songs accessible to everyone. In addition old mbira songs also have to be transcribed so as to preserve them. The study also recommends documentation of mbira playing families.